Potential of the predatory mite Amblyseius herbicolus as biological control agent of Diaphorina citri on plants - Kalile, Milena Oliveira (2024)
Biological control is a sustainable and economically profitable method to control agricultural arthropod pests. However, the biocontrol of phytopathogen vectors can be more complex because it aims not only at the control of pest densities, but also at reducing the incidence of diseases. Here, I investigated the potential of the predatory mite Amblyseius herbicolus Chant (Acari: Phytoseiidae) as biological control agent of Diaphorina citri Kuwayama (Hemiptera: Psyllidae). This psyllid pest is the major vector of the bacteria associated with Huanglongbing (HLB). Previously, A. herbicolus showed high predation rates, reproduction and development when feeding on D. citri eggs. I investigated whether A. herbicolus can also feed on nymphs and reduce densities of D. citri on host plants in the lab (chapter 1) and outside (chapter 2), which may also potentially reduce the spread of HLB. In population dynamics experiments, there was a reduction of c. 85% of D. citri densities in the lab, and 90% on plants outside. In addition, it is crucial to investigate how the presence of predators affects the host plant choice and dispersal of the vector because these have implications for disease transmission. I therefore studied this in the third chapter and observed that D. citri did not avoid plants with predatory mites, not even after having received experience with predators feeding on pest offspring. Besides, the pest did not disperse more from plants with predators feeding on eggs and nymphs than from plants without them. In conclusion, A. herbicolus is a promising biocontrol agent of D. citri. Population dynamics experiments evaluating the effect of this predator on D. citri and HLB incidence on citrus plants in the field need to be done. Keywords: Citrus; Mite; Predator; Psyllid; Vector.